2017
DOI: 10.1016/j.tips.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Precision Medicine: The Ethical Challenges

Abstract: Precision medicine aims to individualize care by understanding differences in genetics, lifestyle, and environment. Pharmacogenomics and cancer genetics represent two promising areas for this approach. Pharmacogenomic tests have the potential to direct drug prescribing to increase safety and effectiveness because individuals vary on a genetic basis in their response to many drugs. Similarly, tests to identify people with an inherited cancer risk can guide prevention. For both, a few tests have entered clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…Moreover, to maintain the quality of healthcare remains problematic issues; and v. Additionally, no systems exist that ensure patients' right regarding financial savings for those diagnostic rest required for PM 101 . Similarly, multiple studies regarding precision medicine concluded that ethical issues regarding data protection and safety 91,102 . Additionally, it also apprehends to future debate about genetically engineered patients and creation for super-human 91 .…”
Section: Changeless Of Precision Medicine In Lowerand Middle-income Cmentioning
confidence: 99%
“…Moreover, to maintain the quality of healthcare remains problematic issues; and v. Additionally, no systems exist that ensure patients' right regarding financial savings for those diagnostic rest required for PM 101 . Similarly, multiple studies regarding precision medicine concluded that ethical issues regarding data protection and safety 91,102 . Additionally, it also apprehends to future debate about genetically engineered patients and creation for super-human 91 .…”
Section: Changeless Of Precision Medicine In Lowerand Middle-income Cmentioning
confidence: 99%
“…No single unifying theme unites this body of work, but a number of diverse themes run through it. In addition to quality improvement, researchers continue to address the challenges of big data in an era of precision medicine, including the provision of tools to help patients and clinicians make good decisions using large amounts of possibly unfamiliar data [6]. Continued expansion of this technology to different clinical contexts, such as emergency medicine, is another hallmark of activity in CDS [7].…”
Section: Introductionmentioning
confidence: 99%
“…Diane Korngiebel, DPhil, University of Washington, is one of several people who are exploring the ethical challenges of precision medicine. 5 COMMENTARY to know the future (genetic markers of cancer in your future) and its challenge to our humanness, is at the heart of many people's reluctance to embrace this new technology. When a patient can get his or her own genetic profile online, complete with diagnoses and carrier states, will primary care physicians be necessary?…”
mentioning
confidence: 99%